Histological results after maxillary sinus augmentation with Straumann® BoneCeramic, Bio-Oss®, Puros®, and autologous bone. A randomized controlled clinical trial - Schmitt, Christian; Döring, Hendrik; Schmidt, Thomas; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objective: This investigation focused on a comparison of clinical and histological characteristics after sinus floor augmentation with biphasic calcium phosphate (BCP, Straumann BoneCeramic®), anorganic bovine bone (ABB, Geistlich Bio-Oss®), mineralized cancellous bone allograft (MCBA, Zimmer Puros®), or autologous bone (AB). Materials and methods: Thirty consecutive patients with a posterior edentulous maxillary situation and a vertical bone height less than or equal to 4 mm were included in this study. A two-stage procedure was carried out. After augmentation of the maxillary sinus with ABB, BCP, MCBA, or AB followed by a healing period of 5 months, biopsies were taken with simultaneous implant placement. The samples were analyzed using microradiography and histology. Results: Ninety-four implants were placed in the augmented positions and 53 bone biopsies were taken and evaluated. The bone volume fraction of newly formed bone was measured as 30.28 ± 2.16% for BCP, 24.9 ± 5.67% for ABB, 41.74 ± 2.1% for AB, and 35.41 ± 2.78% for MCBA with significant increases in bone volume of AB vs. BCP and ABB, and MCBA vs. ABB samples. Significantly different residual bone substitute material was measured as 15.8 ± 2.1% in the BCP group and 21.36 ± 4.83% in the ABB group. Conclusion: As it provides the highest rate of de novo bone formation, AB can be considered to remain the gold standard in sinus floor augmentation. All tested control materials showed comparable results and are suitable for maxillary sinus augmentation.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Biomaterials; Bone regeneration; Bone substitutes; Clinical research; Clinical trials; Guided tissue regeneration; Sinus floor elevation